Artistic functions of Models of Manipulative Speech Interaction in Dialogues of Heroes by F.M. Dostoevsky - Ya. G. Bazhenova (Научный диалог)
The models of manipulative communication in the dialogues of the characters of F. M. Dostoevsky are highlighted in terms of their artistic functions in the narrative. The material for the research is the texts of the novels by F. M. Dostoevsky “Crime and Punishment”, “The Idiot”, “Demons”, “Teenager” and “The Brothers Karamazov”. Particular attention is paid to plot-forming and character-forming functions. It has been established that the plot-forming functions of dialogues with elements of manipulative communication lie in the fact that they psychologically prepare future plot twists or act as a direct impetus to change a particular plot situation, embodying the narrative setting for reticence, silence, hiding “sore spots” in the minds of characters. The analysis revealed that the character-forming functions of dialogues with elements of manipulative communication lie in the artistic embodiment of dramatic relationships between the characters, often at turning points in their lives, when the complex and intense inner life of the character is suddenly revealed to readers. It is shown that the use of certain manipulative techniques by the addressee does not always lead to a violation of the postulates of cooperative communication or the principle of politeness: in a number of cases, manipulation in the addressee's zone may have the goal of just observing the postulate of tact. It is concluded that the use of the analyzed manipulative strategies serves as an artistic means of revealing the character of the hero in speech, when the character, imperceptibly for himself, reveals his inner world to the reader.